Neurosociology - Franks, David D. author. aut Link
XIII, 216 p.
Keywords: Recently, neuroscientists have presented new research which has a direct impact on many areas of Social Psychology. In this innovative volume, the author explores the nexus of Social Psychology and Neuroscience with relation to: -The Human "Self" -The Social Nature of the Mind -Socialization and Language Acquisition -Role-Taking/Theory of Mind -Consciousness -Intersubjectivity -Balanced Social Constructionism -Human Agency -The Effect of Emotion on Rational Decision-Making This groundbreaking work integrates areas of George Herbert Mead's social behaviorism with current neuroscience. The chapters in this volume demonstrate how current work on mirror neurons supports the basic tenets of the American pragmatists' focus on the priority of motor behavior. .